Hadrian's Wall : a study in archaeological exploration and interpretation - Breeze, David J. (Archaeopress Archaeology, 2019)
Based on the annual Rhind Lectures delivered in May 2019, David J. Breeze presents six papers on Hadrian's Wall. He first considers the historiographical background before examining specific aspects: its purpose and operation; its later history; and life on and around the Wall. Finally, he considers the Wall today and some aspects of its future.